2021
DOI: 10.1080/14735903.2021.1976495
|View full text |Cite
|
Sign up to set email alerts
|

Bringing sustainable agricultural intensification practices and technologies to scale through campaign-based extension approaches: lessons from Africa Soil Health Consortium

Abstract: Bringing sustainable agricultural intensification practices and technologies to scale through campaign-based extension approaches: lessons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Research on agricultural research costs up to USD 25.8 billion a year, and it has been reported that pests and diseases now damage almost 40% of the world crops [2]. Due to its widespread adoption across various industries, including agriculture, which faces numerous challenges daily, there has been significant advancement in artificial intelligence over the past 50 years [3,4]. Utilizing pesticides and fertilizers, managing product distribution and storage, managing weeds and illnesses that harm crops, and managing agricultural irrigation and drainage are all tasks that farmers must do [5].…”
Section: Introductionmentioning
confidence: 99%
“…Research on agricultural research costs up to USD 25.8 billion a year, and it has been reported that pests and diseases now damage almost 40% of the world crops [2]. Due to its widespread adoption across various industries, including agriculture, which faces numerous challenges daily, there has been significant advancement in artificial intelligence over the past 50 years [3,4]. Utilizing pesticides and fertilizers, managing product distribution and storage, managing weeds and illnesses that harm crops, and managing agricultural irrigation and drainage are all tasks that farmers must do [5].…”
Section: Introductionmentioning
confidence: 99%
“…Adoption of soil conservation practices is still low in sub-Sahara Africa [22; 23] because smallholder farmers prioritize investing in SLM activities with short-term benefits in terms of improving soil fertility and yields, to the exclusion of practices, whose advantages take longer to realize [22]. The other reason for the low adoption is inadequate extension support to make such technologies recognized and accessible to farmers [23]. Climate variability will continue to negatively affect farm households' welfare and food security in Ghana [24].…”
Section: Introductionmentioning
confidence: 99%